PENYELESAIAN SENGKETA ALTERNATIF PADA KASUS KECELAKAAN PESAWAT UDARA DI INDONESIA - ., Sudiarto (MAJALAH ILMIAH GEMA, 2011)
Apply the principle of presumption of Indonesia Liability in resolving cases of aircraft accidents.  According to this principle, the carrier deemed always responsible for losses unless he could prove that the and/or its employees have taken all necessary measures toavoid losses.  Only a court can decide whether the carrier guilty or not. In the history of aviation in Indonesia plane crash case only Garuda Indonesia plane crash in 1961.  After the case, any aircraft accident compensation settlement settled out of court.      Kata Kunci : Penyelesaian Alternatif, Kasus Kecelakaan, Pesawat Udara.